Scanning tunneling spectroscopy studies of topological materials. (18th March 2020) - Lin, Chun-Liang; Kawakami, Naoya; Arafune, Ryuichi; Minamitani, Emi; Takagi, Noriaki
Abstract: Topological materials have become promising materials for next-generation devices by utilizing their exotic electronic states. Their exotic states caused by spin-orbital coupling usually locate on the surfaces or at the edges. Scanning tunneling spectroscopy (STS) is a powerful tool to reveal the local electronic structures of condensed matters. Therefore, STS provides us with an almost perfect method to access the exotic states of topological materials. In this topical review, we report the current investigations by several methods based on the STS technique for layered topological material from transition metal dichalcogenide Weyl semimetals (WTe2 and MoTe2 ) to two dimensional topological insulators ( layered bismuth and silicene ). The electronic characteristics of these layered topological materials are experimentally identified.